Seroprevalence of Borrelia IgM and IgG Antibodies in Healthy Individuals: A Caution Against Serology Misinterpretations and Unnecessary Antibiotic Treatments - Strizova, Zuzana; Smrz, Daniel; Bartunkova, Jirina (Vector borne and zoonotic diseases (Larchmont, N.Y.), 2020)
In Lyme disease, the interpretation of diagnostic assays is often misunderstood. Cross-reactions of Borrelia proteins with antigens from other bacterial species are well known. Therefore, to diagnose Lyme disease, the finding of positive IgM antibodies must be accompanied by objectively verified clinical signs and a history of a possible tick exposure. Positive Borrelia IgM antibodies in healthy individuals with nonspecific clinical symptoms are likely a false-positive result for Lyme disease and neither long-term antibiotic treatment nor cycling of different antibiotic regimens is beneficial. To date, there is clear evidence that positive serology does not indicate infection with Borrelia species. Borrelia serology has been reported to be positive for months or years in ∼20% of healthy patients who had experienced Lyme disease in the past. Thus, serology as a single diagnostic tool has a very limited value and should be used only to support clinically suspected cases.
Keywords: kousnutí klíštětem; serology; Lyme Disease; imunoglobulin M; Immunoglobulin G; Humans; protilátky bakteriální; Immunoglobulin M; IgM antibodies; Borrelia; Tick Bites; lymeská nemoc; Antibodies, Bacterial; Lyme disease; imunoglobulin G; lidé; diagnosis